Coursebook activities analysis under the perspective of interpersonal function in systemic functional grammar - Scarabelotti, Débora dos Reis (My University, 2019)
This paper was developed to explore how the use of Systemic Functional Grammar can help teachers in English as a Foreign language classes for adult learners. The Systemic Functional Grammar (SFG) was developed by Halliday, who thought about language as more then only a system to be followed, but also how language works with the relation between speaker and listener (or writer and reader). In this paper, the mentioned approach was related with the Communicative Language Teaching (CLT), whose concepts lead teachers to teach with communicative goals, where students can actually relate their studies with meaningful real life situations. To explore how the use of SFG can help teachers, six coursebook activities from three different books were analyzed. The main goal of the analysis is to set up some ideas of how the exercises can work better with a functional perspective from the teachers. From the analysis it was possible to conclude that SFG may be a facilitator tool for teachers to improve book activities when thinking with an interpersonal perspective, making the exercises more meaningful for students in order to make them relate what they are learning with their real life situations, creating an environment in class for them to put in practice what was learned (sic).
Este trabalho foi desenvolvido para explorar como o uso da Gramática Sistêmico-Funcional pode ajudar professores de inglês como língua estrangeira em cursos de idiomas para adultos. A Gramática Sistêmico-Funcional (GSF) foi desenvolvida por Halliday, que pensou na língua como algo a mais do que apenas um sistema a ser seguido, mas também como a linguagem funciona com relação aos falantes e ouvintes (ou escritores e leitores). Neste trabalho, a abordagem mencionada foi relacionada com a Abordagem Comunicativa, a qual os conceitos levam os professores a ensinar com objetivos comunicativos, onde os alunos possam de fato relacionar seus aprendizados com situações reais e significativas. Para explorar como o uso da GSF pode ajudar os professores, seis atividades de três livros didáticos diferentes foram analisados. O principal objetivo da análise foi providenciar algumas ideias de como elas podem funcionar melhor com uma visão funcional pela parte do professor. Pela análise, foi possível concluir que o uso da GSF pode ser um facilitador para os professores ao aprimorar as atividades dos livros, quando são pensadas com uma perspectiva interpessoal, fazendo com que os exercícios fiquem mais significativos para os alunos, para que eles possam relacionar o que estão estudando com situações que acontecem em suas "vidas reais", criando situações em aula para que eles possam colocar em prática o que foi aprendido (sic).
Keywords: Systemic grammar; English language - Study and teaching